2022
DOI: 10.1038/s41598-022-06355-9
|View full text |Cite
|
Sign up to set email alerts
|

A near-natural experiment on factors influencing larval drift in Salamandra salamandra

Abstract: The larval stage of the European fire salamander (Salamandra salamandra) inhabits both lentic and lotic habitats. In the latter, they are constantly exposed to unidirectional water flow, which has been shown to cause downstream drift in a variety of taxa. In this study, a closed artificial creek, which allowed us to keep the water flow constant over time and, at the same time, to simulates with predefined water quantities and durations, was used to examine the individual movement patterns of marked larval fire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Juveniles in the swimming group moved downstream from the initial release section more frequently than those in the SH group. This result is consistent with the general understanding of displacement in other flowsensitive species, such as larval salamanders (Schafft et al, 2022), aquatic invertebrates (Brittain & Eikeland, 1988;Naman et al, 2016), and small fishes (Lechner et al, 2016), where active individuals are more likely to encounter fast currents and thus are at higher risk of downstream displacement. The occurrence of downstream dispersal, on the other hand, could also have been affected by competitive interactions among juveniles because all fish were initially released into the single upstream section of the experimental channel, where the high density of juveniles may have fostered competition.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Juveniles in the swimming group moved downstream from the initial release section more frequently than those in the SH group. This result is consistent with the general understanding of displacement in other flowsensitive species, such as larval salamanders (Schafft et al, 2022), aquatic invertebrates (Brittain & Eikeland, 1988;Naman et al, 2016), and small fishes (Lechner et al, 2016), where active individuals are more likely to encounter fast currents and thus are at higher risk of downstream displacement. The occurrence of downstream dispersal, on the other hand, could also have been affected by competitive interactions among juveniles because all fish were initially released into the single upstream section of the experimental channel, where the high density of juveniles may have fostered competition.…”
Section: Discussionsupporting
confidence: 89%
“…Juveniles in the swimming group moved downstream from the initial release section more frequently than those in the SH group. This result is consistent with the general understanding of displacement in other flow‐sensitive species, such as larval salamanders (Schafft et al, 2022), aquatic invertebrates (Brittain & Eikeland, 1988; Naman et al, 2016), and small fishes (Lechner et al, 2016), where active individuals are more likely to encounter fast currents and thus are at higher risk of downstream displacement.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Small urodela larvae are more prone to drift (Bruce 1985), while upand downstream movements of various distances and with different water velocities have been documented for several species (Johnson & Wallace 2005, Lowe 2008, Cecala et al 2009. In a near-natural experiment, Schafft et al (2022) found that upstream movements of fire salamander larvae did not exceed more than 30 cm.…”
Section: Introductionmentioning
confidence: 94%